Refuge Social Science Debates - Blättel-Mink, Birgit; Noack, Torsten; Onnen, Corinna; Späte, Katrin; Stein-Redent, Rita (Springer Fachmedien Wiesbaden : Imprint: Springer, 2024)
XII, 199 p. 10 illus., 4 illus. in color.